Supplier portfolio selection and order allocation under carbon neutrality: Introducing a "Cool"ing model. (August 2022) - Bai, Chunguang; Zhu, Qingyun; Sarkis, Joseph
Highlights: Supplier selection and order allocation (SSOA) can support carbon neutrality. Formulated multi-objective mathematical model to test practical SSOA policies. Energy power purchasing case optimizes cost, quality and carbon objectives. Realize carbon neutrality through emission offsets and end-of-pipe sequestration. Abstract: Supplier selection and order allocation (SSOA) is an emerging and important issue in supply chain management. SSOA activities can be utilized to mitigate and manage carbon emissions for organizations. SSOA decisions that explicitly consider carbon neutrality or net-zero emissions within the sourcing process are lacking in the literature. This paper introduces a foundational multi-objective mathematical model to bridge this research gap. The model is empirically applied and evaluated using case study information from an energy trading platform that allows for the joint selection of a portfolio of suppliers. Various sourcing policies are evaluated using a reformulation of the foundational model. Parametric analyses provide additional theoretical and practical insights. Findings include the buyer only seeking fossil fuel purchases or virtually ignoring renewable energy usage—reaching net-zero through the purchase of carbon offsets and end-of-pipe carbon emissions sequestration. These and other findings provide theoretical and managerial insights. Additional opportunities for future investigation are relatively extensive for this socio-environmentally crucial issue. Future research guidance on carbon neutrality and net-zero implications for SSOA is provided in this paper.